2019
DOI: 10.1167/tvst.8.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Jogging and Myopia Progression in School Children From Rural Beijing: The Beijing Children Eye Study

Abstract: Purpose To assess the influence of an outdoor program on myopia progression in school children. Methods The prospective interventional school-based study included 373 students aged 6 to 7 years (grade 1 or 2) who were examined annually between 2012 and 2016. Between 2012 and 2013, the children in the study group ( n = 157) performed a 30-minute jogging exercise every school day, while the children in the control school ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…AL findings are consistent with results from cross-sectional and cohort studies on myopia and outdoor time. [58][59][60][61][62] It is unclear what underlying mechanism is responsible for the protective effect of outdoors on limiting eye growth. One possible mechanism is the release of retinal dopamine stimulated by high light levels.…”
Section: Discussionmentioning
confidence: 99%
“…AL findings are consistent with results from cross-sectional and cohort studies on myopia and outdoor time. [58][59][60][61][62] It is unclear what underlying mechanism is responsible for the protective effect of outdoors on limiting eye growth. One possible mechanism is the release of retinal dopamine stimulated by high light levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the human eye generally undergoes a rapid growth from birth to 3 years of age and the variability of refractive error decreases progressively during this period [47], and the greatest increase in eye growth, which is measured by axial length, occurs during the first 10 months of life [48]. Therefore it is speculated that the steady fixation at a specific distance might contribute to myopia for very young children's eyes, and one reason that outdoor activities appear to be beneficial [49][50][51][52] might be that they encourage more frequent shifts of attention and focus. If sufficiently confirmed in further studies, the speculation could provide insight into the mechanism of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…If sufficiently confirmed in further studies, the speculation could provide insight into the mechanism of myopia. Second, a series of studies consistently showed that children who spent more time outdoors were significantly and negatively associated with incident myopia [49][50][51][52], and low illuminance levels indoors can cause myopia in animal models [53]. More time spent indoors watching electronic screens could translate into less time spent outdoors and insufficient exposure to natural light, and thus increase the risk of preschool myopia.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study revealed a potential rebound effect that occurred within three years after stopping of a one-year program with 30 minutes of daily outdoor jogging. 24 Including only children who were myopic at baseline of the study, the intervention was associated with a slight increase in myopia progression.…”
Section: Increased Time Spent Outdoorsmentioning
confidence: 99%